Measuring the Family Quality of Life among Students with Disabilities in Higher Education in the Sultanate of Oman - Ibrahim, Ahmed Thabet Helal; Alhaj, Amjad Hassan; El Sherbiny, Mohamed; Al- Ruqadi, Muadh; Alabri , Rua (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to measure the quality of family life among students with disabilities in higher education in the Sultanate of Oman and its relationship with various variables such as gender, type of disability, access to social security services, age, and academic year. Method: The study adopted the descriptive-analytical approach, and the quality of family life scale issued by the BEACH Center on disability at the University of Kansas is applied. The scale consists of five dimensions: family interaction, parental practices, emotional care, material and physical care, and disability-related support. The validity and reliability of the scale were verified. The study sample consisted of 144 students with disabilities (82 males, 62 females) from Omani higher education institutions. Results: The results indicated that students with disabilities enrolled in higher education institutions in Oman experience a family environment characterized by interaction and communication. They also expressed satisfaction with their parents’ practices toward them and received appropriate and adequate physical and material support at the individual and family levels. In contrast, their satisfaction with the emotional care they and their families receive tended toward neutrality. Conclusion: The current study is an attempt to fill the gap in research related to the quality of family life among students with disabilities in the Sultanate of Oman. The study concluded that there is a need for the Omani Ministry of Higher Education, Research and Innovation to focus on implementing various programs and activities that enhance the quality of family life for their members who are students with disabilities.